Predictors of clinical and microbiological treatment failure in patients with methicillin‐resistant Staphylococcus aureus (MRSA) bacteraemia: a retrospective cohort study in a region with low MRSA prevalence. (13th March 2013) - Forstner, C.; Dungl, C.; Tobudic, S.; Mitteregger, D.; Lagler, H.; Burgmann, H.; Lina, G.
Abstract Invasive infections with methicillin‐resistant Staphylococcus aureus (MRSA) have been associated with increased morbidity and mortality. The aim of the present study was to identify independent predictors of early mortality and treatment failure in patients with MRSA bacteraemia. A total of 132 adult patients who developed MRSA bacteraemia during hospitalization in the University Hospital of Vienna between 2000 and 2011 were screened and 124 were included in a retrospective cohort study. Patient demographics, source of bacteraemia, antimicrobial treatment and microbiological characteristics were evaluated. The 28‐day crude mortality was 30.6%. Predictors of early mortality identified in multivariate Cox regression analysis included higher patient age (adjusted hazard ratio (aHR) 1.03, 95% CI 1.01–1.06, p 0.006), pneumonia (aHR 3.86, 95% CI 1.83–8.12, p <0.001) and failure to use MRSA active treatment (aHR 8.77, 95% CI 3.50–21.93, p <0.001). Ninety‐one (73.4%) patients received glycopeptides as specific MRSA treatment. Of 63 patients treated with vancomycin, only 14 (22.6%) patients had aimed trough levels of 15–20 mg/L. Vancomycin MIC ≥2 mg/L was detected in 28.2% and was associated with glycopeptide pretreatment (p 0.001). All MRSA isolates were susceptible to linezolid and tigecycline. Persistent bacteraemia ≥7 days was documented in 25 (20.2%) patients. Independent determinants for microbiological eradication failure in patients with MRSA bacteraemia included endocarditis (p <0.001) and vancomycin trough levels (p 0.014), but not vancomycin MIC. Failure of clinical and microbiological eradication of MRSA among patients with MRSA bacteraemia was associated with clinical entity rather than with bacterial traits. Pharmacokinetic parameters seem to be decisive on microbiological and clinical success.